Market research for condominium development - 454796 Chua, Anthony Kian Beng (Kuala Lumpur : UTM, 1988)
Condominium, which simply means 'joint ownership' gained tremendous popularity since the introduction of Desa Kudalari believed to be the first condominium in Malaysia, at the end of 1970s. Condominium living potrayed by self-contained facilities and amenities and quality living fast became an alternative form of housing. Prices and rentals began to skyrocketed due to strong demand. However this uptrend was soon curtailed by the economic recession which started in 1984. Demand began to weaken rapidly in the ensuing years, changing the market into a buyer's market - where buyers are very selective and demand value for money. Therefore for new condominiums to suceed, a thorough and detailed study of the market is needed to discover the market's needs and wants. Market research is "a systematic and objective search for and analysis of information relevant to the identification and solution of any problem in the field of marketing". The role of market research is to reduce uncertainty about marketing issues by providing specific, verifiable data about the market, the produser's competition, consumers and their perceptions and the ways the consumers respond to the product. This study has undertaken a market research for condominium development in and around Kuala Lumpur. Fifteen condominiums were selected and analysed on their developments parameters, namely location, floor area, pricing etc. In addition a survey by means of mail questionaires was conducted. It is hope that the findings of this research may act as general guidelines to developers who desire to embark on condominium projects.